Meta-analysis and Trial Sequential Analysis for Therapeutic Eefficacy and Safety of Acupotomy and Acupuncture for Cervical Spondylotic Radiculopathy - Renpan ZHANG; Zhongbiao XIU; Jing LIU; Bin CHEN; Hong LIU; Hongjia ZHAO (康复学报)
Objective:To compare the therapeutic efficacy and safety between acupotomy and acupuncture for cervical spondylotic radiculopathy patients, to provide evidence for clinical practice.Methods:To search in the database, such as PubMed, Cochrane, China Biomedical Literature Database(CBM), China Knowledge Network Database(CNKI), Chinese Scientific Journal Database(VIP)and Wanfang Database. Clinical randomized controlled trials(RCTs)of acupotomy versus acupuncture with/without additional treatment for cervical spondylotic radiculopathy patients would be searched by two reachers independently. The time limitation was from the commencement of each database to 31st October 2018. The total effective rate and curative rate would be assessed as the primary outcomes. Visual analogue scale and clinical symptom score would be assessed as the secondary outcome. After selected, the included data were analyzed by Review Manager 5.3 software for meta-analysis and TSA V 0.9 software for trial sequential analysis(TSA).If P≤0.1 of 2 test or I2>50%indicated statistically significant heterogeneity, a random-effect model would be used. Otherwise, we would calculate using a fixed effects model. Continuous outcomes would be presented as the mean difference(MD)with 95% confidence interval(CI), while dichotomous data would be presented as relative risk(RR)with 95% CI.Results:A total of 10 RCT trials involving 727 patients were eventually included. The meta-analyses demonstrated that the total effective rate of the acupotomy group was significantly higher than that of the acupuncture group [RR=1.09,95% CI(1.04,1.14),P=0.0 006<0.005],and TSA results showed that the cumulative Z-values confirmed the results of meta-analysis through traditional boundary value and TSA threshold. The curative rate of acupotomy group was higher than that of acupuncture group [RR=1.54,95%CI(1.27,1.87),P<0.0 001],and TSA results showed that the cumulative Z-values confirmed the results of meta-analysis through traditional boundary value and TSA threshold. The VAS score [MD=-0.70,95%CI(-0.97,-0.43),P<0.00 001] and clinical symptom score [MD=1.20,95%CI(0.69,1.72),P<0.00 001] after treatment had statistical significance between acupotomy group and acupuncture group.Conclusion:Acupotomy is more effective than acupuncture in the treatment of cervical spondylotic radiculopathy. However, due to low quality and limited sample size of included studies, further well-designed RCTs with high quality are still needed to evaluate the beneficial effects of acupotomy.